Stable low-temperature dry reforming of methane over mesoporous La2O3-ZrO2 supported Ni catalyst - Sokolov, Sergey; Kondratenko, Evgenii V.; Pohl, Marga-Martina; Barkschat, Axel; Rodemerck, Uwe (Applied catalysis. B, Environmental, 2012)
[Display omitted] ► Supported Ni catalysts for dry reforming of methane at 400°C have been developed. ► Ni supported on mesoporous ZrO2-La2O3 is active and stable for 180h. ► Ni supported on non-structured and macroporous ZrO2-La2O3 deactivates. ► Major deactivation mechanism is covering Ni particles by graphene and surface oxidation of Ni. ► Ni sintering does not appear to play a significant role in deactivation. A series of supported Ni catalysts was prepared using various supports and tested in low-temperature (400°C) dry reforming of methane. Ni/La2O3-ZrO2 showed near-to equilibrium yields of CO and H2 and the highest stability. This catalyst was studied in greater detail in order to determine the influence of the support morphology on the catalyst activity and stability. To this end, nonstructured, mesoporous, and macroporous La2O3-ZrO2 were prepared and characterized before and after loading with Ni. Among them, only Ni on the mesoporous support showed practically no change in activity over 180h on-stream, whereas the others deactivated. Formation of graphene-like coke layers on the catalysts and of NiO shell over Ni particles appears to be responsible for catalyst deactivation, while sintering of Ni did not play a major role. The enhanced stability of Ni on the mesoporous La2O3-ZrO2 is attributed to stronger interaction of the Ni particles with the support stemming from a pore confinement effect.